Determinan Pengembangan Usaha Mikro Berkelanjutan Pada Komunitas Etnis Madura: Peranan Kesiapan Manajemen Mutu Dan Keuangan Bisnis - Melvin Rahma Sayuga Subroto; Andreas Mahendro Kuncoro; Bayu Seto (Jurnal Akuntansi Manado (JAIM), 2024)
This study aims to analyze the influence of quality management and financial management on innovation strategy and its impact on business sustainability, with ethnic communities as a moderating variable. The method employed is Partial Least Squares Structural Equation Modeling (PLS-SEM) based on higher-order constructs. Data were collected from 237 small business owners of the Madurese ethnic community in Yogyakarta. The results indicate that financial management significantly affects innovation strategies, which ultimately support business sustainability. Innovation strategies were found to be a crucial mediator in this relationship. Moreover, ethnic communities strengthen the relationship between innovation strategies and business sustainability through their social networks and cultural values. This study offers theoretical and practical contributions, emphasizing the importance of synergy between financial management, innovation strategies, and ethnic communities in supporting SME sustainability.